Biochemical Serum Changes in the Liver and Kidney of Hyperuricemia Rats Exposed to Ethanolic Leaf Extract of Hantap (Sterculia coccinea Jack) - Yuliet; Rhizky S Auliana; Miranti; Ni Luh Rindiani; Marzelany M Sombolinggi; Khildah -; Khaerati (Jurnal Penelitian Pendidikan IPA, 2025)
High uric acid levels can increase oxidative stress in the kidneys causing glomerular damage and tubular ischemia. In addition, it also causes hepatocyte injury so that uncontrolled hyperuricemia will cause liver damage. This study aims to determine the effect of Hantap leaf extract (Sterculia coccinea Jack) on kidney and liver function in rat hyperuricemia. This study was a quasi-experimental study with a post-test only control group design. This study used 30 rats induced with chicken liver juice and potassium oxonate and then given Hantap leaf ethanol extract therapy at doses of 100, 200 and 400 mg/kg BW. Data on urea, creatinine, SGOT and SGPT levels were statistically tested using the ANOVA and Post-hoc Duncan tests. While data on uric acid levels used the T test and Anova. Significantly different results compared to negative controls were found in the group given Hantap leaf extract at doses of 100, 200 and 400 mg/kg BW on uric acid, creatinine, ureum, SGOT and SGPT levels. The results of the study prove that administering Hantap leaf extract can improve kidney and liver function in hyperuricemic rats.